Transcriptional control of cell density dependent regulation of matrix metalloproteinase and TIMP expression in breast cancer cell lines - Bachmeier, Beatrice E.; Vené, Roberta; Iancu, Cristina M.; Pfeffer, Ulrich; Mayer, Barbara; Noonan, Douglas; Albini, Adriana; Jochum, Marianne; Nerlich, Andreas G. (Thrombosis and Haemostasis, 2005)
Our recent studies on breast carcinoma cell lines with differing tumorigenicity / invasiveness (MCF-7< MDA-MB-468< MDAMB-231< MDA-MB-435) had shown significantly decreasing expression levels of MMPs-1,-2,-3,-8,-9,-10,-11 and –13 with increasing cell density while the levels of TIMP-1 and –2 increased. This correlated well with a lower invasiveness of confluent cells. In the present study, we extend our in vitro studies on three-dimensional cultures of breast cancer cell lines MCF-7 and MDAMB-435 and the transcriptional control of MMP and TIMP-expression in two-dimensional cultures of MDA-MB-231 and –435 cells. The tumor spheroid model showed that MMP expression and proteolytic activity were considerably higher in loosely structured tumor groups as compared to densely growing “compact” cell complexes. These data suggested that cell density regulates MMP and TIMP transcription and therefore, we tested whether AP-1, NFκB and CRE are involved in this process. Gene silencing of c-jun in sparse cultures had an inhibitory effect on MMP-3,–9 and –13 expression, on proteolytic activity as well as on the invasive potential of the cells, thus confirming a role for AP-1. TIMP-1, and –2 expression was up-regulated as compared to control cells. Consistent with this, overexpression of c-jun and c-fos in confluent breast cancer cell lines leads to up-regulation of MMP expression, proteolytic activity and invasion as well as down-regulation of TIMP-1. In summary, we provide evidence that cell density influences the invasive potential of tumor cells via regulation of MMPs and TIMPs by AP-1, NFκB and CRE transcription factors. Overexpression of MMPs in sparse cultures could help explain early dissemination of potentially metastatic cells.
Keywords: Breast cancer cell lines; MMP-regulation; gene silencing; invasion; cell density